Thrombopoietin-receptor agonists for adult patients with immune thrombocytopenia: a narrative review and an approach for managing patients fasting intermittently - Yassin, Mohamed A.; Al-Rasheed, Mona; Al-Khaboori, Murtadha; Marashi, Mahmoud; Osman, Hani; Wali, Yasser; Al Kindi, Salam; Alsayegh, Faisal; Provan, Drew (Frontiers in Cardiovascular Medicine, 2023)
restrictions. In cases where romiplostim and avatrombopag are unavailable, patients should be educated on the appropriate administration, possible interactions, and dietary restrictions before initiating eltrombopag.Immune thrombocytopenia is an autoimmune disease characterized by transient or persistent thrombocytopenia and increased bleeding tendency. The goals of treatment of ITP included preventing severe bleeding episodes, maintaining an optimal platelet level, minimizing treatment toxicity, and optimizing health-related quality of life. Thrombopoietin-receptor agonists are used for patients who fail to respond to glucocorticoids or have a recurrent decrease in platelet count after glucocorticoids are discontinued. Thrombopoietin-receptor agonists include romiplostim, eltrombopag, and avatrombopag, all approved for treating immune thrombocytopenia. These agents have demonstrated a high response rate in clinical trials. In this article, we review the efficacy and safety results of each agent, and highlight the effect of fasting on their response knowing that each agent has a different pharmacokinetic profile, particularly food-drug interaction. We provide an expert opinion that may assist in managing the administration of such agents during intermittent fasting (e.g., Ramadan fasting).